Does social media activism actually work? Exploring the persuasive effects of social media activism against racism in Singapore - Yap, Chelsea Ning Rei (Nanyang Technological University, 2022)
Social media activism is a relatively recent phenomenon that has taken off in Singapore, where many have taken to social media platforms to relay messages on issues such as racism. However, the effectiveness of such activism has yet to be studied in depth; our paper thus seeks to examine whether social media activism instigates any persuasive effects, informed by Self-Categorisation Theory (SCT) and collective action framing. Analysing the results of the online experiment with a sample size of N = 150, it was observed that there were strong interaction effects between SCT and collective action framing on increasing message persuasiveness, while effects on electronic-word-of-mouth (eWOM) intentions were marginally significant. With further analysis of the interaction effects, messages promoted by outgroup members were found to be statistically significant in instigating higher eWOM intentions and persuasiveness, while messages from the ingroup revealed no such effects. From these findings, the present study provides actionable insights to improve the effectiveness of social media activism in Singapore and advance literature on social movements and their relevant theories.